2020
DOI: 10.1177/1120672120922453
|View full text |Cite
|
Sign up to set email alerts
|

Five-year results of viscotrabeculotomy versus conventional trabeculotomy in primary congenital glaucoma: A randomized controlled study

Abstract: Purpose To assess the long-term results of viscotrabeculotomy in infants with primary congenital glaucoma and to compare its outcome with conventional trabeculotomy. Patients and methods A prospective randomized comparative study included infants with primary congenital glaucoma younger than 2 years. Patients were divided into two groups: viscotrabeculotomy group and conventional trabeculotomy group. Preoperative and postoperative intraocular pressures, corneal diameter, intraoperative and postoperative compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 17 publications
4
17
0
Order By: Relevance
“…18 The IOP outcome in the VT group reported in this study is comparable to that reported for VT by the authors in other studies. 5 The success rates reported in this study emphasize the fact that angle surgery is highly successful in controlling IOP in PCG. An advantage for VCST over VT is exemplified by the higher success rates, and more so; the higher percentage of complete success (with less dependence on IOP-lowering medications in the VCST group than in the VT group), though not statistically significant.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…18 The IOP outcome in the VT group reported in this study is comparable to that reported for VT by the authors in other studies. 5 The success rates reported in this study emphasize the fact that angle surgery is highly successful in controlling IOP in PCG. An advantage for VCST over VT is exemplified by the higher success rates, and more so; the higher percentage of complete success (with less dependence on IOP-lowering medications in the VCST group than in the VT group), though not statistically significant.…”
Section: Discussionsupporting
confidence: 54%
“…and followed a standard protocol which was previously described by the authors. 5 Perkin's handheld applanation tonometer (Haag Streit USA and Reliance Medical Products, Mason, OH) was used for IOP measurement with the eyes central just after the induction of GA. Because of the known effect of inhalational GA of IOP reduction, if PCG was suspected with a low measured IOP, serial follow-ups were scheduled to monitor progression of corneal diameter, axial length, and optic disc cupping to establish the diagnosis of PCG. The children were then scheduled for surgery and the eyes randomly assigned (using simple randomization by flipping a coin) for the procedure of "Visco-Circumferential Suture Trabeculotomy" (VCST) or "Viscotrabeculotomy" (VT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For rigid-probe SEVT, the surgical technique was previously described in details. 9 Postoperative treatment included topical ofloxacin and dexamethasone 5 times daily with gradual tapering over 1 month. Timolol and/or dorzolamide drops were administered twice daily when needed.…”
Section: Surgical Techniquementioning
confidence: 99%
“…VT was shown to be at least as effective and as safe as conventional probe trabeculotomy for the reduction of IOP in PCG. 8,9 Circumferential trabeculotomy (CT) provides complete rupture of the TM and Schlemm canal (SC) inner wall, with better improvement in IOP reduction than rigid-probe single-entry trabeculotomy. 7 Different techniques of CT are now available in PCG management with improved success including illuminated microcatheter-assisted CT, 360degree suture trabeculotomy, visco-circumferential-suturetrabeculotomy (VCST), and rigid-probe double-entry trabeculotomy.…”
mentioning
confidence: 99%